Early Evidence of Circulating SARS-CoV-2 in Unvaccinated and Vaccinated Measles Patients, September 2019–February 2020 - Paixao, Joana (2022)
Funding Information: This study was funded as a donation from the Ministry of Health, Angola. Publisher Copyright: © 2022 Paixao et al.